2019
DOI: 10.1016/j.jcjo.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Atypical late presentation of galactosemia

Abstract: clinical picture changes significantly-in this case when the patient's CRP re-elevated while developing a cough-and not just attribute the change to re-activation of GCA. Following the above referenced rheumatology studies, the inclusion of TCZ in the treatment of initial and refractory cases of GCA in treatment guidelines should be strongly considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Although most CG patients present with severe clinical manifestation in early infancy, rare cases of late-onset atypical CG have been reported. Simpson et al [2019] reported a case of atypical classic galactosemia diagnosed at the age of 7 years with findings of poor academic performance at school and vision problems due to bilateral cataracts. The patient had a family history of galactosemia, and the CG diagnosis was confirmed through a genetic analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most CG patients present with severe clinical manifestation in early infancy, rare cases of late-onset atypical CG have been reported. Simpson et al [2019] reported a case of atypical classic galactosemia diagnosed at the age of 7 years with findings of poor academic performance at school and vision problems due to bilateral cataracts. The patient had a family history of galactosemia, and the CG diagnosis was confirmed through a genetic analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Most galactosemia patients present in the neonatal period with clinical findings of feeding intolerance, vomiting, diarrhea, jaundice, weight loss, and lethargy, while hepatomegaly, excessive bleeding, cataract, and E. coli septicemia may also develop [Anderson, 2018;Cerone and Rios, 2019]. Atypical manifestations of galactosemia in children and adults have been reported previously [Weits-Binnerts et al, 1993;Kisa et al, 2019;Simpson et al, 2019]. Diagnosis is confirmed from measurements of galactose-1-phosphate levels and GALT enzyme activity and through a molecular genetic analysis [Saudubray et al, 2012;Welling et al, 2017;Anderson, 2018].…”
Section: Introductionmentioning
confidence: 92%